Effect of Rational Emotive Behavioral Therapy on Preventive Measures of Transmission In The Family of Pulmonary Tb Patients - Firdausi, Nugrahaeni; Yuliansari, Pratiwi; Yektiningsih, Erwin (Universitas STRADA Indonesia, 2020)
Background: Pulmonary TB is an infectious disease caused by mycobacterium tuborkulosis and is contagious. The family of pulmonary TB patients plays a very important role in the transmission of pulmonary TB disease. Preliminary data collection shows that four out of five (80%) families of pulmonary TB sufferers so far have gained knowledge about the transmission of pulmonary TB, but in their daily use personal protective equipment is rarely used. The family said they rarely wear masks because they feel fine without the masks, the family also feels wearing masks will hurt the feelings of people with pulmonary TB.Purpose: This study aimed to determine the effect of Rational Emotive Behavior Therapy on preventive measures for transmission of patients with pulmonary TB.Methods: This study used a quasy experiment research design with a non-randomized control group design pretest-posttest approach. The sample in this study was the family of pulmonary TB patients at UPTD Puskesmas Puhjarak Kediri who met the inclusion and exclusion criteria, with a sampling technique using purposive sampling. The independent variable of this study was Rational Emotive Behavioral Therapy and the dependent variable was family preventive measures. The instrument used to measure preventive measures for pulmonary TB transmission is a questionnaire which contains 12 questions, and for the independent variable of memory therapy is SAK research. The research data were processed using the Wilcoxon signed ranks test and Mann-Whitney. Alternative hypotheses are accepted if p <0.05.Results: The results showed that the Mann Whitney test results in the treatment and control groups at the time of the pretest showed a value of p = 0.690 and at the posttest was p = 0.000. Wilcoxon signed rank test results show in the treatment group after treatment p = 0.005, while in the control group when posttest was p = 0.317.Conclusion: The results of the assessment of preventive measures for pulmonary TB transmission between the treatment group and the control group after the implementation of Rational Emotive Behavioral Therapy showed that there were differences in the value of preventive measures for pulmonary TB transmission between the treatment group and the control group after receiving Rational Emotive Behavioral Therapy